2023
DOI: 10.1186/s40001-023-01007-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of oral and vaginal misoprostol on labor induction: updating a systematic review and meta-analysis of interventional studies

Abstract: Objectives This study is aimed to compare the effect of oral misoprostol with vaginal misoprostol to induce labor as a systematic review and meta-analysis. Methods Electronic databases including PubMed [Medline], Scopus, Web of science, Embase, Ovid, Cochrane library, and ClinicalTrials.gov were searched using the relevant keywords. All RCTs comparing the effect of oral vs vaginal misoprostol on labor induction were considered. The Cochrane Risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This contrasts with studies that have found a higher frequency of caesarean sections in women who received oral misoprostol compared to vaginal misoprostol. 5,6 Fortunately, none of the women in any of the groups had developed uterine hyperstimulation. However, there was an increase in the number of women who developed PPH in the sequential group (OM-VM) but we could not compute a statistical difference.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This contrasts with studies that have found a higher frequency of caesarean sections in women who received oral misoprostol compared to vaginal misoprostol. 5,6 Fortunately, none of the women in any of the groups had developed uterine hyperstimulation. However, there was an increase in the number of women who developed PPH in the sequential group (OM-VM) but we could not compute a statistical difference.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, another systematic review has shown that the risk of meconiumstained amniotic fluid (MSAF) and caesarean sections were higher in women who took oral misoprostol in comparison to those who received the drug vaginally. 4,5 Moreover, a study conducted by Handal-Orefice et al has concluded that women who received 50 mcg oral misoprostol every 4-6 hours up to a maximum of 6 doses had a higher risk of caesarean delivery compared to those who received 25 mcg vaginal misoprostol in the same dosing interval. 6 Therefore, standardization of misoprostol dose schedules and routes of administration is necessary to reduce primary caesarean section rates during labor induction.…”
mentioning
confidence: 99%
“…A more recently published systematic review comparing oral versus vaginal misoprostol for labor induction 44 identified 33 trials from systematic database‐searching between January 1990 and January 2022. These included the 13 trials we included in the present review.…”
Section: Discussionmentioning
confidence: 99%
“…The presented data suggest that vaginal misoprostol has a low complication rate. However, on the other hand, studies show that the use of vaginal misoprostol may be associated with an increased percentage of uterine hyperstimulation [ 51 , 52 , 53 ]. Additionally, the differences in the results may probably be due to the different designs of the studies and the different ways of dosing vaginal misoprostol.…”
Section: Discussionmentioning
confidence: 99%